Weather Information for Tribune - H. D. Bond; R. Mai (Kansas Agricultural Experiment Station Research Reports, 2015)
Tribune, Kansas: In 2014, annual precipitation of 16.31 in. was recorded, which is 1.59 in. below normal. Seven months had below-normal precipitation. June (3.61 in.) was the wettest month. The largest single amount of precipitation was 1.54 in. on July 30.
Keywords: weather; Tribune; Kansas; rain; snowfall; temperatures